Value orientation of public elementary and secondary school administrators - Yadao, Ruben D. 1940- (1988)
The value orientations man-nature-value, activity value, time value and relational value of 112 elementary and 39 secondary school principals from Manila, Quezon City, Pasay City, Zambales, Tarlac and Isabela were investigated. The dominant patterns are Mastery-over-Nature, Being-in-Becoming, Past Orientation, and Individualism. Value orientations were affected by many administrator characteristics and activities.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Values; School administrators